TERMINALIA ARJUNA TRANSDERMAL MATRIX FORMULATION CONTAINING DIFFERENT POLYMER COMPONENTS: TERMINALIA ARJUNA TRANSDERMAL MATRIX FORMULATION - DINANATH GAIKWAD,; NAMDEO JADHAV, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this research work was to prepare a transdermal matrix formulation containing different polymer components for topical delivery. Methods: Terminalia arjuna bark extract loaded transdermal patches were prepared using solvent casting technique with different amount of chitosan and Eudragit RL 100 batches were prepared according to 32 factorial designs. Results: The transdermal patches prepared were evaluated for different physicochemical properties, determination of drug content, in vitro diffusion study, ex vivo study, skin irritation study, and stability study. Infrared studies indicate the absence of chemical interaction or any changes in the chemical composition of extract during the preparation of transdermal patch. In vitro diffusion study and ex vivo diffusion study of optimized batch S3 showed drug releases to 74.56–69.12%, respectively, up to 12 h. Skin irritation study indicates that the extract and excipients used in the patch do not show any irritating effect on the skin. All the prepared transdermal matrix formulations were found to be stable on storage. Conclusion: It can be concluded that prepared matrix formulation containing different polymer components can be used for transdermal delivery for the treatment of chronic ailments such as cardiovascular disorder.